Obstetric Near Miss Events in a Tertiary Research Level Teaching Hospital - Khatun, Tarannum; Rahman, Zarin; Parveen, Nuzhat; Ansari, Akhtar Alam; Mansuri, Mohammed Islam; Chaurasia, Anand Kumar (Med Phoenix, 2017)
Background: Objective of the study was to identify the important causes of near miss cases and to evaluate the key interventions for the management and ultimate maternal outcome. Material and methods: In this case series study, critically ill pregnant, laboring or postpartum women who were admitted either directly or through referral to the National Medical College, Birgunj, Nepal, formed the study group. The women who escaped death due to medical or surgical interventions were categorized as Near Miss. These cases were defined based on WHO Criteria 2009. Results: There were 2424 births during this year and 33 were near miss cases. The bulk of these were directly admitted to our hospital (23 cases). The most common condition leading to this dreadful condition was hemorrhage, acute severe hypertensive disorder (preeclampsia/eclampsia) and sepsis. Disseminated Intravascular Coagulation was found to be the most common organ dysfunction. Emergency hysterectomy was the most frequent surgical intervention used to prevent mortality. Conclusion: Maternal Near Miss review is a viable review as it has potential to highlight the deficiency as well as positive elements of obstetric services in any health system. Hemorrhage followed by hypertensive disorders are the leading causes of near miss events. Med Phoenix Vol.2(1) July 2017, 44-47